Aconitine induces autophagy via activating oxidative DNA damage-mediated AMPK/ULK1 signaling pathway in H9c2 cells. (10th January 2022) - Wang, Wenlin; Jiang, Jialuo; Huang, Yan; Peng, Fu; Hu, Tingting; Wu, Jiayang; Pan, Xiaoqi; Rao, Chaolong
Abstract: Ethnopharmacological relevance: Aconitum species, with a medicinal history of 2000 years, was traditionally used in the treatment of rheumatism, arthritis, bruises, and pains. However, many studies have reported that Aconitum species can cause arrhythmia in experimental animals, resulting in myocardial fibrosis and cardiomyocyte damage. Cardiotoxicity is the main toxic effect of aconitine, but the detailed mechanism remains unclear. Aim of the study: This study aimed to explore the effects and underlying mechanism of autophagy in H9c2 cardiomyocytes induced by aconitine. Materials and methods: H9c2 cells were incubated with different concentrations of aconitine for 24 h, and the intervention sections were pretreated with various inhibitors for 1 h. The effects of aconitine on the oxidative DNA damage, autophagy and viability of H9c2 cells were evaluated by flow cytometry, confocal microscopy, enzyme-linked immunosorbent assay and Western blot. Results: In H9c2 cells, the cell viability declined, LDH release rate, the number of autophagosomes, protein expression levels of LC3 and Beclin-1 increased significantly after 24 h of aconitine incubation. The pretreatment of autophagy inhibitor 3-MA decreased markedly autophagosomes and protein expression levels of LC3 and Beclin-1, which suggested that aconitine could induce cell autophagy. The significant increase of ROS and 8-OHdG showed that aconitine could cause oxidative DNA damage through ROS accumulation. Meanwhile, treatment of aconitine dramatically increased AMPK Thr172 and ULK1 Ser317 phosphorylation, and Compound C inhibited AMPK Thr172 and ULK1 Ser317 phosphorylation, which proved that aconitine induced autophagy via AMPK activation mediated ULK1 phosphorylation. Antioxidant NAC significantly reduced LDH, ROS and 8-OHdG, inhibited the phosphorylation of AMPK Thr172 and ULK1 Ser317, and down-regulated autophagosomes and proteins expression levels of LC3 and Beclin-1. Consequently, the inhibition of oxidative DNA damage and AMPK/ULK1 signaling pathway alleviated the aconitine-induced autophagic death of H9c2 cells. Conclusions: These results showed that aconitine induces autophagy of H9c2 cardiomyocytes by activating AMPK/ULK1 signaling pathway mediated by oxidative DNA damage. The autophagy induced by aconitine in cardiomyocytes is dependent on the activation of the AMPK pathway, which may provide novel insights into the prevention of aconitine-related toxicity. Graphical abstract: Image 1